Quality of life after hysterectomy and uterus-sparing hysteroscopic management of abnormal uterine bleeding or heavy menstrual bleeding - Sushma Selvanathan; Neema Acharya; Sonakshi Singhal (Wolters Kluwer Medknow Publications, 2019)
Study Objective: To compare the effect on quality of life (QOL) of uterus-sparing hysteroscopic targeted therapy with that of hysterectomy as therapeutic surgical procedure for heavy menstrual bleeding (HMB). Methods/Methodology: This was a prospective observational study. Setting: Endoscopy unit, Department of Obstetrics and Gynecology, Datta Meghe Institute of Medical Sciences Wardha, Maharashtra, India. Patients: A total of 354 women meeting inclusion and exclusion criteria were included in the study, of which 178 women had undergone hysteroscopic targeted therapy while 176 women had undergone abdominal hysterectomy as surgical treatment for HMB. Interventions: Group I - Hysteroscopic surgical procedure - polypectomy, endometrial resection, myomectomy. Group II - Hysterectomy - abdominal hysterectomy, vaginal hysterectomy, laparoscopic hysterectomy.) Results: Health-related QOL assessed by Short Form 36 questionnaire response score was significantly better for women who underwent hysteroscopic targeted therapy was significantly better at both short-term and long-term follow-up. Conclusions: Both hysteroscopic procedures and hysterectomy when used as therapeutic modality for abnormal uterine bleeding/HMB (AUB/HMB) improve the quality of life when used as therapeutic option, and the improvement in QOL is significantly different at 6 months and 1 year while the improvement in QOL 1 week after surgery is better in hysteroscopy group when compared to hysterectomy group suggesting early improvement in QOL when hysteroscopic therapies are used as treatment modality for surgical management of HMB/AUB.